Efficacy and Safety of Teneligliptin in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Xiaoxuan; Huang, Xuefei; Bai, Chongfei; Qin, Dalian; Cao, Shousong; Mei, Qibing; Ye, Yun; Wu, Jianming (Frontiers in Pharmacology, 2018)
Background: Teneligliptin is a 3rd-generation dipeptidyl peptidase-4 (DPP-4) inhibitor. There is a limited evidence regarding the effect of teneligliptin. Therefore, this study is to assess the efficacy and safety of teneligliptin in type 2 diabetes mellitus (T2DM) patients with inadequately glycemic controlled. Methods: A search of PubMed, Medline, Embase, and The Cochrane Library during 2000.01 to 2018.03 was performed for randomized controlled trials of teneligliptin compared to placebo in patients with T2DM with monotherapy or add-on treatment. Results: Ten trials with 2119 patients were analyzed. Teneligliptin produced absolute reductions in glycated hemoglobin A1c (HbA1c) levels (weighted mean difference (WMD) 0.82%, 95% confidence interval (CI) [-0.91 to -0.72], p < 0.00001) compared with placebo. However, after 36-42 weeks of follow-up (open-label), HbA1c level rise higher than duration (double-blind) in teneligliptin group. Teneligliptin led to greater decrease of fasting plasma glucose (FPG) level (vs. placebo, WMD -18.32%, 95% CI [-21.05 to -15.60], p < 0.00001). Teneligliptin also significantly decreased the 2 h postprandial plasma glucose (2 h PPG) (WMD -46.94%, 95% CI [-51.58 to -42.30], p < 0.00001) and area under the glucose plasma concentration-time curve from 0 to 2 h (AUC0-2h) for PPG (WMD -71.50%, 95% CI [-78.09 to -64.91], p < 0.00001) compared with placebo. Patients treated with teneligliptin achieved increased homeostasis model assessment of β cell function (HOMA-β) with 9.31 (WMD, 95 % CI [7.78 to 10.85], p < 0.00001). However, there was no significant difference between teneligliptin and placebo in overall adverse effects (0.96 risk ratio (RR), 95 % CI [0.87, 1.06], p = 0.06). The risks of hypoglycemia were not significantly different between teneligliptin and placebo (1.16 RR (95 % CI [0.59, 2.26], p = 0.66). Conclusions: Teneligliptin improved blood glucose levels and β-cells function with low risk of hypoglycemia in patients with T2DM. Common adverse effects of teneligliptin including hypoglycemia were identified and reviewed. Risks of cardiovascular events are less certain, and more data for long-term effects are needed.